Method of Restoration of Input Signals of Nonlinear Dynamic Object with Destributed Parameters - Ivaniuk, V.,; Ponedilok, V. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2018)
The article deals with the method of signal restoration at the input of a nonlinear dynamic object with distributed parameters. To describe these objects, a universal mathematical model in the form of a Volterra integro-degree series has been chosen. The problem of signal restoration is reduced to the problem of solving the Volterra polynomial equation of the first kind. The numerical implementation of such models is suggested to be carried out using quadrature methods, in particular, the method of trapezoids. In order to increase the stability of the solution in the presence of noise interference in the input data, it is suggested to use the differential regularization operator, which allows the incorrectly set task to be transformed into a class of correct ones.